2020
DOI: 10.5713/ajas.18.0933
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of proteolytic microorganisms and their effects on proteolysis in total mixed ration silages of soybean curd residue

Abstract: Objective: The objective of this study was to isolate proteolytic microorganisms and evaluate their effects on proteolysis in total mixed ration (TMR) silages of soybean curd residue. Methods: TMRs were formulated with soybean curd residue, alfalfa or Leymus chinensis hay, corn meal, soybean meal, a vitamin-mineral supplement, and salt in a ratio of 25.0: 40.0:30.0:4.0:0.5:0.5, respectively, on a basis of dry matter. The microbial proteinases during ensil ing were characterized, the dominate strains associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…In terms of forage crops, especially for high-protein herbages, it is inevitable that large quantities of true protein are converted into NPN during ensiling, resulting in poor nitrogen utilization for ruminants. In the present study, NPN content in all silages increased rapidly during the first 7 days of ensiling, as supported by Hao et al [ 34 ] in TMR silages. However, higher NPN content with lower silage pH in RY36 compared with RY0 is in agreement with Sousa et al [ 35 ], who reported that protein breakdown during ensiling can be reduced by a rapid decrease in silage pH.…”
Section: Discussionsupporting
confidence: 89%
“…In terms of forage crops, especially for high-protein herbages, it is inevitable that large quantities of true protein are converted into NPN during ensiling, resulting in poor nitrogen utilization for ruminants. In the present study, NPN content in all silages increased rapidly during the first 7 days of ensiling, as supported by Hao et al [ 34 ] in TMR silages. However, higher NPN content with lower silage pH in RY36 compared with RY0 is in agreement with Sousa et al [ 35 ], who reported that protein breakdown during ensiling can be reduced by a rapid decrease in silage pH.…”
Section: Discussionsupporting
confidence: 89%
“…Meanwhile, the activity of arginase, a key enzyme in the urea cycle 45 , was also obviously lower than that in natural silage. According to the findings of Hao et al 46 , protein-degrading bacteria in silage mainly included Curtobacterium, Bacillus, Paenibacillus , Enterococcus, Pediococcus and Lactiplantibacillus , with the highest proteinase activity in Bacillus, Enterococcus , Clostridium and Enterobacter . According to the results, free amino acids produced by microorganisms through protein hydrolysis should be balanced with their amino acid and nucleotide metabolism as available nitrogen sources.…”
Section: Discussionmentioning
confidence: 98%
“…( 2022 ), who disclosed that Weissella , accompanied by a certain proportion of Serratia and Pantoea presented in graminaceous crop (whole‐plant corn). As another dominant genera, Curtobacterium was proved as the proteolytic bacteria in the alfalfa and Leymus chinensis silages (Hao et al., 2020 ). Gharechahi et al.…”
Section: Discussionmentioning
confidence: 99%
“…This agrees with the result of Bai et al (2022), who disclosed that Weissella, accompanied by a certain proportion of Serratia and Pantoea presented in graminaceous crop (whole-plant corn). As another dominant genera, Curtobacterium was proved as the proteolytic bacteria in the alfalfa and Leymus chinensis silages (Hao et al, 2020). Gharechahi et al (2017) ever stated that the microbial community, which develops during the fermentation process, varies distinctly from that of epiphytic one.…”
Section: Microbial Communities Of Oat Silagesmentioning
confidence: 99%